Upaya Pencegahan Kejahatan Melalui Satuan Keamanan Lingkungan - Amin, Rahman; Haryani Putri, Anggreany; Hadrian, Endang; Wardana, Ali; Pramudya Tama, Audy; Novega, Lidya; Narima Ambarrini, Diah Narima Ambarrini (Abdi Bhara, 2024)
Crime is a shadow of human civilization that follows the dynamics of human life which today is increasing both in quantity and quality caused by various factors that require appropriate prevention efforts, one of which is by empowering community members in Environmental Security Unit activities as a form of self-initiative security carried out voluntarily by the community. But in fact, the community still does not know and understand well the urgency of the Environmental Security Unit in preventing crime, so it is important to carry out community service activities in the form of legal counseling on crime prevention efforts through the Environmental Security Unit. The target of community service activities in the form of counseling is people living in Cimuning Village, Mustika Jaya District, Bekasi City. The implementation of community service activities generally consists of the preparation stage, implementation stage, evaluation stage, and reporting of the output of activities. The results of this community service activity, First, that the activity ran smoothly which was attended by community members in Cimuning Village enthusiastically. Second, that the activities have increased knowledge and understanding to community members about crime prevention efforts through the Environmental Security Unit.